Analyzing the Legal Reasoning behind the Prohibition of Cryptocurrency Transactions in Indonesian Fatwa and Regulations - Prabowo, Bagya Agung; Nurjihad; Rohidin (Al-Manahij: Jurnal Kajian Hukum Islam, 2025)
This study analyzes the legal rationale underlying the prohibition of cryptocurrency transactions in Indonesia, particularly through the Indonesian Ulema Council (MUI) fatwa and the government's regulatory framework. While MUI's fatwa bans cryptocurrency as a medium of exchange and investment due to elements of gharar, maysir, and unclear underlying value, Indonesian state regulations classify cryptocurrency as a tradable commodity under the supervision of the Commodity Futures Trading Regulatory Agency (Bappebti). This duality creates a normative tension between religious legal reasoning and positive law. Using a doctrinal and analytical approach, this research examines the basis of MUI's arguments, the extent to which cryptocurrency fits the criteria of lawful (halal) transactions in Islamic law, and how government regulation frames cryptocurrency within Indonesia's financial and digital economy policies. The findings indicate that MUI's prohibition is grounded in risk, volatility, and speculative characteristics, whereas the government adopts a pragmatic regulatory stance by focusing on consumer protection and market oversight. This study contributes to the ongoing discourse on harmonizing religious fatwas and state law in emerging digital financial technologies.